A Study the Aluminum Doped Zinc Oxide Thin Films - Yacine Aoun; Boubaker Benhaoua; Said Benramache (Журнал нано- та електронної фізики)
We investigated the optical properties of pure and Aluminum doped zinc oxide thin films as the n-type semiconductor. In this paper, we have studied the deposition of Al doped ZnO thin films on glass substrate at 350 °C, when the films were deposited with 0, 2 and 3 wt using spray pyrolysis technique. % of Al / Zn, the substrates were heated using the solar cells method. The substrate was R217102 glass in a size of 30 × 17.5 × 1 mm. All films exhibit an average optical transparency about 85 %, in the visible region. The shift of optical transmittance towards higher wavelength can be showed by the increase of band gap energy from 3.245 to 3.281 eV with increasing of Al doping from 0 to 3 wt. %. The Urbach energy Eu increase and decrease reaching to optimal value was obtained after doping at 3 wt. %.